Mycotoxin concentrations in rice are affected by chalkiness, grain shape, processing type, and grain origin - Tang, E.N.; Ndindeng, S.A.; Onaga, G.; Ortega-Beltran, A.; Falade, T.D.O.; Djouaka, R.F.; Frei, M. (2025)
Mycotoxins such as aflatoxins (AFs), fumonisins (FBs), zearalenone (ZEN), and deoxynivalenol (DON) pose a risk to public health due to their carcinogenic potency (AFs and FBs) and anti-nutritional effects. The hazards associated with mycotoxins are accentuated where food management practices, control, and regulatory systems from farm to plate are sub-optimal. Information on the frequency of these mycotoxins in rice commercialized in markets in sub-Sahara Africa (SSA) is limited. The current study examined AF concentrations in 527 rice samples collected from 54 markets in five SSA countries. Grain quality characteristics, processing methods, and origin of samples were contrasted with toxin levels. In total, 72% of the samples had detectable AFs levels (range = 3.0 to 89.8 μg/kg). Forty-seven percent (47%) of the samples had AFs above 4 μg/kg, the European Union maximum level (ML), and were evaluated for cooccurrence with FBs, ZEN, and DON. Total AFs and ZEN cooccurred in 40% of the samples, and 30% of the positive ZEN samples had concentrations above the ML of 75 μg/kg. Total AFs did not co-occur with FBs and DON. Multivariate analysis revealed that length-to-width ratio (p < 0.0001), mixed variety for width (p = 0.04), and chalkiness (p = 0.009) significantly influenced aflatoxin concentrations. Slender grains had higher AFs concentrations than bold and medium grains (p < 0.0001). Possible strategies to mitigate mycotoxin contamination in rice include improving grain quality traits and practicing proper drying and hermetic storage before and after milling. These findings provide valuable insights for both domestic and international actors in establishing and strengthening regulations and management systems to mitigate rice mycotoxin contamination.